Manufacturing method of copper-clad laminate
By employing a roll-to-roll electrolytic plating process with a non-energized upstream area and an electrolytic downstream area, the method addresses the issue of white haze in copper-clad laminates, achieving a wider effective width and improved manufacturing efficiency.
Patent Information
- Application Number
- JP2025012056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-11
AI Technical Summary
The existing methods for manufacturing copper-clad laminates, particularly those used in flexible printed wiring boards, face challenges in forming thin copper plating coatings without causing white haze or cloudiness at the edges, which reduces the effective width of the laminate.
The method involves using a roll-to-roll electrolytic plating process where the upstream area of the plating tank is set to a non-energized state, and the downstream area is used for electrolytic plating, allowing for the formation of a thin copper plating coating without white haze.
This approach effectively suppresses white haze at the edges of the copper plating coating, resulting in a copper-clad laminate with a wider effective width and improved manufacturing efficiency.
Smart Images

Figure 2025061876000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a copper-clad laminate. More specifically, the present invention relates to a method for producing a copper-clad laminate used in the manufacture of flexible printed circuit boards (FPCs) and the like. [Background technology]
[0002] Flexible printed wiring boards in which wiring patterns are formed on the surface of a resin film are used in electronic devices such as liquid crystal panels, notebook computers, digital cameras, mobile phones, etc. Flexible printed wiring boards are manufactured from, for example, copper-clad laminates.
[0003] The metallizing method is known as a method for manufacturing copper-clad laminates. Manufacturing copper-clad laminates by the metallizing method is carried out, for example, in the following procedure. First, a base metal layer made of a nickel-chromium alloy is formed on the surface of a resin film. Next, a copper thin film layer is formed on the base metal layer. Next, a copper plating film is formed on the copper thin film layer. The conductor layer is thickened by copper plating until it has a thickness suitable for forming a wiring pattern. By the metallizing method, a copper-clad laminate of the type known as a two-layer board, in which a conductor layer is formed directly on a resin film, is obtained.
[0004] A flexible printed wiring board is obtained by forming a wiring pattern on a copper-clad laminate by a semi-additive method, a subtractive method, or the like. The manufacturing of a flexible printed wiring board by the semi-additive method is performed in the following procedure (see Patent Document 1). First, a resist layer is formed on the surface of the copper plating film of the copper-clad laminate. Next, openings are formed in the resist layer in the portions where the wiring pattern is to be formed. Next, electrolytic plating is performed using the copper plating film exposed from the openings in the resist layer as the cathode to form a wiring portion. Next, the resist layer is removed, and the conductor layer other than the wiring portion is removed by flash etching or the like. This results in a flexible printed wiring board. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-278950 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the semi-additive method, unnecessary portions of the conductor layer of the copper-clad laminate are removed by etching. If the conductor layer is too thick, the etching time will be long and the etching of the wiring portion will also progress, making it difficult to make the cross-sectional shape of the wiring rectangular. Therefore, it is preferable that the conductor layer of the copper-clad laminate processed by the semi-additive method is thin. Specifically, the thickness of the copper plating film is generally set to 0.2 to 1.0 μm. On the other hand, the copper-clad laminate processed by the subtractive method is required to have a relatively thick copper plating film. The thickness of the copper plating film of the copper-clad laminate processed by the subtractive method is generally 8 to 12 μm.
[0007] The copper plating film on copper-clad laminates can be formed using a roll-to-roll plating device. Plating devices capable of forming thick copper plating films with a thickness of 8 to 12 μm have long plating tanks to ensure sufficient plating time. It is difficult to form thin copper plating films with a thickness of 0.2 to 1.0 μm using such plating devices.
[0008] Therefore, the inventors of the present application attempted to form a thin copper plating film by conveying the substrate in a non-energized state in a part of the plating tank, so-called "empty conveyance", rather than electrolytic plating over the entire length of the plating tank. However, empty conveyance in a part of the plating tank sometimes caused the edge of the copper plating film to become cloudy white. The cloudy white area had a poor appearance and could not be used as a product, narrowing the effective product width of the copper clad laminate.
[0009] In view of the above circumstances, an object of the present invention is to provide a method for producing a copper-clad laminate that can suppress the occurrence of whitish tarnish on the edges of a copper plating film. [Means for solving the problem]
[0010] A method for producing a copper-clad laminate according to one embodiment of the present invention involves transporting a substrate from the upstream end to the downstream end of a plating tank by roll-to-roll means while forming a copper plating film on the surface of the substrate by electrolytic plating to obtain a copper-clad laminate, the method being characterized in that an upstream area including the upstream end of the plating tank is an empty transport area set to a no-current state, and the remaining downstream area is an electrolytic area in which current is passed between an anode and the substrate to perform electrolytic plating. Effect of the Invention
[0011] According to the present invention, it is possible to suppress the occurrence of whitish tarnish at the edges of the copper plating film, and to manufacture a copper-clad laminate having a wide effective product width. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a cross-sectional view of a copper-clad laminate. [Diagram 2] FIG. [Diagram 3] FIG. 2 is a front view of a substrate being transported in a plating tank. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Next, an embodiment of the present invention will be described with reference to the drawings. As shown in Fig. 1, a copper-clad laminate 1 produced by a method according to one embodiment of the present invention comprises a substrate 10 and a copper plating film 20 formed on the surface of the substrate 10. The copper plating film 20 may be formed on only one side of the substrate 10 as shown in Fig. 1, or the copper plating film 20 may be formed on both sides of the substrate 10.
[0014] The copper plating film 20 is formed by electrolytic plating. Therefore, the substrate 10 may be made of any material that has electrical conductivity on the surface on which the copper plating film 20 is formed. For example, the substrate 10 is made of a base film 11 having insulating properties and a metal layer 12 formed on the surface thereof. The base film 11 may be a resin film such as a polyimide film or a liquid crystal polymer (LCP) film. The metal layer 12 is formed by, for example, a sputtering method. The metal layer 12 is made of a base metal layer 13 and a copper thin film layer 14. The base metal layer 13 and the copper thin film layer 14 are laminated in this order on the surface of the base film 11. In general, the base metal layer 13 is made of nickel, chromium, or a nickel-chromium alloy.
[0015] Although not particularly limited, the thickness of the base film 11 is generally 12.5 to 37 μm. The thickness of the undercoat metal layer 13 is generally 5 to 50 nm. If a thick copper thin film layer 14 is to be formed by sputtering, the conveying speed becomes slow and the manufacturing cost becomes high. Therefore, the thickness of the copper thin film layer 14 is usually 50 to 150 nm.
[0016] The undercoat metal layer 13 may be omitted. The copper thin film layer 14 may be formed on the surface of the base film 11 via the undercoat metal layer 13, or may be formed directly on the surface of the base film 11 without the undercoat metal layer 13.
[0017] The copper plating film 20 is formed on the surface of the thin copper layer 14. Although not particularly limited, the thickness of the copper plating film 20 is generally 0.2 to 1.0 μm in the case of a copper-clad laminate 1 processed by a semi-additive method. The metal layer 12 and the copper plating film 20 are collectively referred to as the "conductor layer."
[0018] The copper plating film 20 can be formed by a roll-to-roll plating apparatus. The plating apparatus is an apparatus that performs electrolytic plating on the long strip-shaped substrate 10 while transporting the substrate 10 by roll-to-roll. The plating apparatus has a supply device that pays out the substrate 10 wound in a roll, and a winding device that winds up the substrate 10 (copper-clad laminate 1) after plating into a roll.
[0019] A pre-treatment tank, a plating tank 30, and a post-treatment tank are arranged on the transport path of the substrate 10. While the substrate 10 is transported through the plating tank 30, a copper plating film 20 is formed on the surface of the substrate 10 by electrolytic plating. In this way, a long strip-shaped copper-clad laminate 1 is obtained.
[0020] As shown in FIG. 2, the plating tank 30 is a single tank that is long horizontally along the transport direction of the substrate 10. The substrate 10 is transported over the entire length of the plating tank 30, that is, from the upstream end 30u to the downstream end 30d of the plating tank 30. Here, the upstream end 30u is the end where the substrate 10 is introduced into the plating tank 30. The downstream end 30d is the end where the substrate 10 is discharged from the plating tank 30. The substrate 10 is transported along the center of the plating tank 30. A copper plating solution is stored in the plating tank 30. The substrate 10 transported inside the plating tank 30 is entirely immersed in the copper plating solution.
[0021] The copper plating solution contains a water-soluble copper salt. Any water-soluble copper salt that is generally used in copper plating solutions may be used without any particular limitation. As the water-soluble copper salt used in the copper plating solution, one selected from inorganic copper salts, copper salts of alkane sulfonic acids, copper salts of alkanol sulfonic acids, copper salts of organic acids, etc. may be used alone or in combination of two or more. However, from the viewpoint of management of the copper plating solution, it is preferable to use one type of water-soluble copper salt alone.
[0022] The copper plating solution may contain sulfuric acid. The pH and sulfate ion concentration of the copper plating solution can be adjusted by adjusting the amount of sulfuric acid added. The copper plating solution may contain additives that are generally added to plating solutions. Examples of additives include a brightener component, a leveler component, a polymer component, and a chlorine component. One type selected from these additives may be used alone, or two or more types may be used in combination.
[0023] The content of each component in the copper plating solution can be selected arbitrarily. However, the copper plating solution preferably contains 15 to 70 g / L of copper and 20 to 250 g / L of sulfuric acid. In this way, the copper plating film 20 can be formed at a sufficient speed. The copper plating solution preferably contains 1 to 50 mg / L of a brightener component. In this way, the precipitated crystals can be made fine and the surface of the copper plating film 20 can be made smooth. The copper plating solution preferably contains 1 to 300 mg / L of a leveller component. In this way, protrusions can be suppressed and a flat copper plating film 20 can be formed. The copper plating solution preferably contains 10 to 1,500 mg / L of a polymer component. In this way, current concentration on the edge of the substrate 10 can be alleviated and a uniform copper plating film 20 can be formed. The copper plating solution preferably contains 20 to 80 mg / L of a chlorine component. In this way, abnormal deposition can be suppressed.
[0024] The temperature of the copper plating solution is preferably 20 to 35° C. In addition, it is preferable to stir the copper plating solution in the plating tank 30. The means for stirring the copper plating solution is not particularly limited, but a means using a jet flow can be used. For example, the copper plating solution can be stirred by spraying the copper plating solution jetted from a nozzle onto the substrate 10.
[0025] Inside the plating tank 30, a plurality of anodes 31 are arranged along the transport direction of the substrate 10. As shown in FIG. 3, inside the plating tank 30, the substrate 10 is suspended with one edge along the transport direction facing up and the other edge facing down, and is transported by a plurality of clamps 32, 33 that grip both edges. The clamp 32 that grips the upper edge of the substrate 10 is connected to a power supply device and also functions as a cathode. By passing a current between the anode 31 and the clamp 32 (cathode), a copper plating film 20 can be formed on the surface of the substrate 10.
[0026] 2, anodes 31 are disposed on both the front and back sides of the substrate 10. Therefore, by using a substrate 10 having a metal layer 12 formed on both sides of a base film 11, it is possible to form a copper plating film 20 on both sides of the substrate 10.
[0027] A rectifier is connected to each of the multiple anodes 31 disposed inside the plating tank 30. Therefore, it is possible to set a different current density for each anode 31.
[0028] The thickness of the copper plating film 20 obtained by electrolytic plating is basically determined from the current density and plating time. Specifically, as shown in the following formula (1), 2 ], plating time T [min], and coefficient k to obtain thickness D [μm]. Here, coefficient k is a value that depends on conditions such as the copper plating solution, and is determined by testing. D = k × J × T (1)
[0029] The copper-clad laminate 1 processed by the semi-additive method preferably has a thin copper plating film 20 with a thickness of 0.2 to 1.0 μm. As can be seen from formula (1), the thickness D of the copper plating film 20 can be reduced by lowering the current density J or shortening the plating time T. However, if the current density J is made too low, the surface roughness of the copper plating film 20 increases. In addition, if the current density J is made too low, the amount of additive-derived components such as sulfur that are taken up by the copper plating film 20 increases, and the properties of the copper plating film 20, such as the solubility and conductivity, become different from the target ones. Therefore, the current density J needs to be high to a certain extent. The plating time T can be adjusted by the conveying speed of the substrate 10. However, since the length of the plating tank 30 is constant, there is a limit to shortening the plating time T.
[0030] Therefore, the inventors of the present application attempted to form a thin copper plating film 20 by shortening the effective length of the plating tank 30. Normally, electricity is passed through all the anodes 31 arranged in the conveying direction of the substrate 10, and electrolytic plating is performed over the entire length of the plating tank 30. Instead of this, some of the anodes 31 are in a non-energized state, i.e., the current density is set to 0 A / dm 2 In this way, a part of the plating tank 30 becomes an empty transport zone where the substrate 10 is transported in a non-energized state, and the effective length of the plating tank 30 is shortened. This shortens the plating time T, and a thin copper plating film 20 can be formed.
[0031] Incidentally, the copper coating does not dissolve easily unless it is in an oxidized state. However, when the flow of the copper plating solution is strong in a non-energized state, the copper coating tends to dissolve only in that portion. Therefore, when an empty transport area is provided in the plating tank 30, it is preferable to perform electrolytic plating in the upstream area of the plating tank 30 from the viewpoint of preventing dissolution of the copper thin film layer 14. Also, it is preferable to perform electrolytic plating in the downstream area of the plating tank 30 from the viewpoint of preventing dissolution and discoloration of the formed copper plating film 20. Therefore, if a portion of the plating tank 30 is to be the empty transport area, it is preferable to perform electrolytic plating in the upstream and downstream areas of the plating tank 30 and to use the intermediate area between them as the empty transport area.
[0032] However, when the middle zone of the plating tank 30 was used as the empty transport zone, a phenomenon was confirmed in which the edge of the copper plating film 20 became cloudy and whitish. Specifically, as shown in Figure 3, the copper plating film 20 became cloudy and whitish in an area of about 20 mm from the lower edge.
[0033] Although many aspects of the cause of the edges of the copper plating film 20 becoming cloudy and whitish remain unclear, the inventors of the present application speculate as follows. In a roll-to-roll plating device, adjacent anodes 31 are separated, allowing different current densities to be set for each anode 31. However, because the cathodes (substrate 10) are connected, when a current is applied between the anode 31 and substrate 10 in some upstream and downstream areas, a weak current also flows through the substrate 10 in the intermediate area where no current is applied. When abnormal deposition occurs due to a weak current, numerous fine bumps appear on the surface of the copper plating film 20, which causes the film to appear cloudy and whitish.
[0034] Therefore, the inventors of the present application checked the occurrence of whitish clouding of the copper plating film 20 while changing the position of the empty transport zone in the plating tank 30. As a result, they found that the whitish clouding of the edge of the copper plating film 20 can be suppressed under specific conditions.
[0035] That is, as shown in Fig. 2, the upstream zone in the plating tank 30 may be defined as the empty zone TZ, and the downstream zone may be defined as the electrolysis zone EZ. Here, the upstream zone (empty zone TZ) is a part of the upstream side including the upstream end 30u, and the downstream zone (electrolysis zone EZ) is the remaining (downstream) zone following the upstream zone and reaching the downstream end 30d. In the empty zone TZ, the current density of the anode 31 is set to 0 A / dm 2 The length of the empty transport zone TZ is set to a current density of 0 A / dm 2 In the electrolysis zone EZ, the current density of the anode 31 is set to 0 A / dm 2 A larger value is set, and a current is passed between the anode 31 and the substrate 10 to perform electrolytic plating.
[0036] When set as described above, during the plating period in which the substrate 10 is transported from the upstream end 30u to the downstream end 30d, the substrate 10 is transported in an unenergized state during the initial period, and electrolytic plating is performed during the remaining period.
[0037] By setting such conditions, it is possible to suppress cloudiness at the edges of the copper plating film 20. As a result, the edges of the copper clad laminate 1 do not have poor appearance, and a copper clad laminate 1 with a wide effective product width can be manufactured. EXAMPLES
[0038] (Common conditions) The substrate was prepared in the following procedure. A polyimide film (Upilex-35SGAV1 manufactured by Ube Industries) with a thickness of 35 μm was prepared as the base film. The base film was set in a magnetron sputtering device. A nickel-chromium alloy target and a copper target were installed in the magnetron sputtering device. The composition of the nickel-chromium alloy target was 20 mass % Cr and 80 mass % Ni. Under a vacuum atmosphere, a 25 nm thick undercoat metal layer made of a nickel-chromium alloy was formed on both sides of the base film, and a 100 nm thick copper thin film layer was formed thereon.
[0039] Next, a copper plating film was formed on both sides of the substrate by electrolytic plating using a roll-to-roll plating device. The copper plating solution stored in the plating tank contained 120 g / L of copper sulfate, 70 g / L of sulfuric acid, 16 mg / L of brightener component, 20 mg / L of leveler component, 1,100 mg / L of polymer component, and 50 mg / L of chlorine component. Bis(3-sulfopropyl) disulfide (a reagent manufactured by RASCHIG GmbH) was used as the brightener component. Diallyldimethylammonium chloride-sulfur dioxide copolymer (PAS-A-5 manufactured by Nittobo Medical Co., Ltd.) was used as the leveler component. Polyethylene glycol-polypropylene glycol copolymer (UNILUBE 50MB-11 manufactured by NOF Corporation) was used as the polymer component. Hydrochloric acid (35% hydrochloric acid manufactured by Wako Pure Chemical Industries, Ltd.) was used as the chlorine component.
[0040] The temperature of the copper plating solution was set to 31° C. During electrolytic plating, the copper plating solution was agitated by spraying the copper plating solution from a nozzle substantially perpendicularly to the surface of the substrate. The tension of the substrate transported in the plating tank was set to 85 N / m.
[0041] The appearance of the obtained copper-clad laminate was checked to see whether there was any white haze on the edge of the copper plating film, and the width of the white haze. Here, as shown in Figure 3, the width W of the white haze means the width of the area where the white haze was confirmed from the lower edge of the copper plating film.
[0042] Example 1 The upstream area in the plating tank is set as the empty area, and the current density is set to 0 A / dm 2 The downstream section was the electrolysis section. The current densities in the electrolysis section were 0.7, 1.0, 1.2, and 1.4 A / dm 2 The current density was increased stepwise in this order. The specific current density conditions are shown in Table 1. The transport time of the substrate in the empty transport area was 1.0 min.
[0043] As a result, a copper plating film with a thickness of 0.2 μm was formed, and no white cloudiness was observed on the edge of the copper plating film.
[0044] Example 2 The current density conditions were as shown in Table 1. The transport time of the substrate in the empty transport zone was 1.0 minute. As a result, a copper plating film with a thickness of 0.5 μm was formed. In addition, no whitish cloudiness was observed on the edge of the copper plating film.
[0045] Example 3 The current density conditions were as shown in Table 1. The transport time of the substrate in the empty transport zone was 1.0 minute. As a result, a copper plating film with a thickness of 0.9 μm was formed. In addition, no whitish cloudiness was observed on the edge of the copper plating film.
[0046] Example 4 The current density conditions were as shown in Table 1. The transport time of the substrate in the empty transport zone was 0.1 minutes. As a result, a copper plating film with a thickness of 0.5 μm was formed. In addition, no whitish cloudiness was observed on the edge of the copper plating film.
[0047] Example 5 The current density conditions were as shown in Table 1. The substrate was transported for 2.0 minutes in the empty transport zone. As a result, a copper plating film with a thickness of 0.5 μm was formed. No white haze was observed on the edge of the copper plating film.
[0048] Example 6 The current density conditions were as shown in Table 1. The substrate was transported for 3.0 minutes in the empty transport zone. As a result, a copper plating film with a thickness of 0.5 μm was formed. No white haze was observed on the edge of the copper plating film.
[0049] In Examples 1 to 6, in which the upstream zone in the plating tank was the empty transport zone and the downstream zone was the electrolysis zone, no whitish clouding was observed on the edge of the copper plating film. It was confirmed that, at least under conditions in which the transport time of the substrate in the empty transport zone was 0.1 to 3 minutes, the whitish clouding on the edge of the copper plating film could be sufficiently suppressed.
[0050] [Table 1]
[0051] In addition, when empty transport is performed in the upstream area of the plating tank, there is a concern that the copper thin film layer may dissolve. In particular, the part where the jet of copper plating solution hits is prone to dissolution. In order to confirm the degree of dissolution of the copper thin film layer, the substrate was passed through the plating tank in a non-energized state, and the thickness of the copper thin film layer where the jet of copper plating solution hits was confirmed. As a result, it was confirmed that the copper thin film layer becomes thinner when the empty transport exceeds 8 minutes. Conversely, dissolution of the copper thin film layer can be prevented if the empty transport is within 8 minutes. Therefore, it can be said that dissolution of the copper thin film layer can be prevented by setting the transport time of the substrate in the empty transport area to 3 minutes or less as in Examples 1 to 6.
[0052] Comparative Example 1 Electrolytic plating was carried out in the upstream and downstream sections of the plating tank, and the intermediate section was designated the empty transport section. The specific current density conditions are as shown in Table 2. The substrate was transported for 1.0 min in the empty transport section.
[0053] As a result, a copper plating film with a thickness of 0.5 μm was formed. A 20 mm wide white haze appeared on the edge of the copper plating film. This confirmed that a white haze would appear on the copper plating film if the intermediate zone was used as an empty transport zone.
[0054] [Table 2]
[0055] Comparative Example 2 The upstream zone in the plating tank was the electrolysis zone, and the downstream zone following the upstream zone was the empty zone. There was no intermediate zone. The specific current density conditions are as shown in Table 3. The substrate was transported for 1.0 min in the empty zone.
[0056] As a result, a copper plating film with a thickness of 0.5 μm was formed. A white haze with a width of 16 mm was also formed on the edge of the copper plating film. This confirmed that a white haze would occur on the copper plating film even when the downstream zone following the upstream zone was set as a dry transport zone.
[0057] [Table 3] [Explanation of symbols]
[0058] 1 Copper-clad laminate 10 Base material 11 Base film 12 metal layer 13 Undercoat metal layer 14 Copper thin film layer 20 Copper plating film 30 Plating tank 31 Anode 32, 33 Clamp
Claims
1. In obtaining a copper-clad laminate, a copper plating film is formed on a surface of the substrate by electrolytic plating while the substrate is transported from an upstream end to a downstream end of a plating tank by a roll-to-roll method, An upstream zone including the upstream end of the plating tank is an empty transport zone set in a non-energized state, and the remaining downstream zone is an electrolysis zone in which current is applied between the anode and the substrate to perform electrolytic plating. A method for producing a copper-clad laminate comprising the steps of:
2. The transport time of the substrate in the empty transport zone is 0.1 to 3 minutes. The method for producing a copper-clad laminate according to claim 1 .
Citation Information
Patent Citations
Method for monitoring in-line insulation in continuous electrical treatment device for metal wire and strip material
JP1994002196A
Method for producing two layer circuit board by plating process and plating device therefor
JP2007246962A
Multi-tank electrolytic copper plating method and method of manufacturing electromagnetic wave shielding material
JP2011179079A
Plating apparatus for metal-coated resin substrate
JP2012201944A
Copper-clad laminated sheet, and method of producing copper-clad laminated sheet
JP2019167583A